2014
DOI: 10.1007/s10719-014-9522-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the impact of GFP tagging on Robo1-heparin interaction

Abstract: Green fluorescent proteins (GFPs) and their derivatives are widely used as markers to visualize cells, protein localizations in in vitro and in vivo studies. The use of GFP fusion protein for visualization is generally thought to have negligible effects on cellular function. However, a number of reports suggest that the use of GFP may impact the biological activity of these proteins. Heparin is a glycosaminoglycan (GAG) that interacts with a number of proteins mediating diverse patho-physiological processes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…16 An affinity resin was prepared by binding of a biotinylated fusion protein of human Robo1 and GFP to a streptavidin−agarose column. Recently, it was shown that GFP can bind HS, 17 and therefore an additional affinity resin for HS depletion was prepared containing biotinylated GFP alone. First, the natural HS mixture was passed through the GFP depletion column in a low-salt buffer (0.15 M NH 4 OAc, pH 7.4) to capture GFP-binding HS sequences, and the unbound flow-through and low-salt wash was collected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16 An affinity resin was prepared by binding of a biotinylated fusion protein of human Robo1 and GFP to a streptavidin−agarose column. Recently, it was shown that GFP can bind HS, 17 and therefore an additional affinity resin for HS depletion was prepared containing biotinylated GFP alone. First, the natural HS mixture was passed through the GFP depletion column in a low-salt buffer (0.15 M NH 4 OAc, pH 7.4) to capture GFP-binding HS sequences, and the unbound flow-through and low-salt wash was collected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An expression vector encoding the human roundabout homolog 1 precursor (Robo1, NP_002932, Uniprot Q9Y6N7) Ig domains 1 and 2 (residues 58–266) in the pGEn2 vector was previously described [36]. The vector encodes a fusion protein with an NH2-terminal signal sequence followed by an 8xHis tag, AviTag [37], “super-folder” GFP [38], the TEV protease recognition site [39], and the Ig1-2 domains of Robo1.…”
Section: Methodsmentioning
confidence: 99%
“…However, seldom dissected are the plausible negative structural and functional ramifications of attaching the sizeable, ~ 27 kDa GFP moiety to the protein of interest. Indeed, in many instances, GFP-tagging has been shown to generate unstable fusion products 4 , 5 , cause aberrant protein localization 6 , promote aggregation 7 , prevent assembly 8 , and/or perturb protein function in more than subtle ways 9 12 . Such scrutiny has never been imposed on GFP-tagged dynamin-related protein 1 (Drp1), a long-studied yet controversial mechanoenzymatic GTPase recruited from the cytosol to the mitochondrial surface to mediate mitochondrial division 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%